PELAKSANAAN PEMBAGIAN KERJA DALAM PENINGKATAN EFEKTIVITAS KERJA PADA KANTOR PENGADILAN NEGERI SIBOLGA - Koto, Mhd. Shafwan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the implementation of the division of labor in increasing work effectiveness at the Sibolga District Court Office by appealing to the hioptesis that there is an influence of the division of labor on increasing work effectiveness at the Sibolga District Court Office. The research method used is a causal comperative descriptive method. The author uses 31 respondents as samples taken from the entire population. The results showed a positive relationship between the Division of Work with Work Effectiveness at the Sibolga District Court Office of 0.757, so that if interpreted on a scale of values ​​can be categorized as a strong relationship. The regression equation obtained Y = 9,419 + 0.782 X which shows the effect of the division of labor on work effectiveness, which means the effectiveness of work will increase by a regression coefficient / slop (0.782) if the division of labor variables are added by one unit. The t test showed that the hypothesis was accepted to be correct, where t count 6.233> 2.04523. While the coefficient of determination is known that the division of labor only accounts for 57.3% of work effectiveness at the Sibolga District Court Office and the remaining 42.7% is influenced by other factors not examined.